Hybrid Ni3N-nitrogen-doped carbon microspheres (Ni3N@C) in situ derived from Ni-MOFs as sensitive non-enzymatic glucose sensors. (16th April 2021) - Chen, Junli; Yin, Haoyong; Zhou, Jielin; Wang, Ling; Ji, Zhenguo; Zheng, Yifan; Nie, Qiulin
ABSTRACT: Metal organic frameworks derived hybrid microspheres consisted of Ni3 N and nitrogen-doped carbon were prepared by a facile in situ nitridation process. The as prepared Ni3 N@C electrocatalysts displayed superior performance for non-enzymatic glucose sensing with two linear detection ranges. The sensitivity in the lower detection range (0.001–3 mM) is 1511.59 μ AmM −1 cm −2 with detection limit of 0.3 μM. The sensitivity in higher detection range (3–7 mM) is calculated to be 783.75 μ A mM −1 cm −2 . The excellent electrochemical performance of Ni3 N@C for glucose sensing was mainly attributed to its fast charge transfer ability stemming from the synergistic effect of nitrogen-doped carbon and uniform dispersed Ni3 N nanoparticles. Furthermore, the as constructed Ni3 N@C sensor also showed good feasibility for glucose detection in serum sample and acceptable recovery in analysis. Thus, the preparation of Ni3 N@C may hold a new promise for designing highly sensitive non-enzymatic glucose sensors.